АНАЛІЗ КОНКУРЕНТОСПРОМОЖНОСТІ ПІДПРИЄМСТВ СФЕРИ ПОСЛУГ Й ОСНОВНІ НАПРЯМИ ЇЇ ПІДВИЩЕННЯ - Burtovska, Viktoriia; Klimova, Inna (Zhytomyr Ivan Franko State University, 2024)
The article analyzes the interpretation of the concept of "competition" by various authors. It has been found that this concept currently does not fully meet the criteria of systematization and comprehensiveness, which makes it difficult to definitively determine whether competition is a process, a state, an aspiration, or another category. It has been proven that many existing definitions do not encompass competition as a phenomenon inherent not only to economic but also to social, production, and even biological systems. The conducted research has shown that it is advisable to study the relationship between competitiveness at the country level, individual enterprises, and specific products, as competitiveness is a synthesis of many economic categories. It has been proven that managing the competitiveness of an enterprise is a specific aspect of enterprise management, the goal of which is to form, develop, and realize competitive advantages and ensure the viability of the enterprise as a subject of higher-level economic competition. To manage the level of competitiveness, the enterprise must create a system of measures that will significantly influence the level of competitiveness to bring it to an optimal or desired state and maintain this state in the future. The article presents the results of a PEST analysis of the studied enterprise, identifying factors that have a positive and negative impact on the cleaning services market in Zhytomyr and the company LLC "KlinMarket" in particular. The analysis of the competitive environment showed that LLC " KlinMarket" does not lag behind its competitors in all compared characteristics. The article contains recommendations for increasing the competitiveness of  LLC " KlinMarket" namely: choosing a differentiation strategy, focusing on internet presence, implementing innovations, and paying attention to human resources, as the company experiences staff turnover. To improve the competitiveness management system, it is necessary to introduce effective tools for market and competitor analysis, optimize internal processes, and promote personnel development. This will allow the company to quickly respond to market changes and maintain competitive advantages.